Bipolar Electrochemical Synthesis of WS2 Nanoparticles and Their Application in Magneto‐Immunosandwich Assay. (23rd April 2016) - Mayorga‐Martinez, Carmen C.; Khezri, Bahareh; Eng, Alex Yong Sheng; Sofer, Zdeněk; Ulbrich, Pavel; Pumera, Martin
Abstract : WS2 nanoparticles are prepared using bipolar electrochemistry. Obtained material exhibits high activity for hydrogen evolution reaction (HER) and it is used as a label in standard magneto‐immunosandwich assay for protein detection through HER. This new system shows high analytical performance in terms of a wide range, selectivity, sensitivity, and reproducibility. Abstract : WS2 nanoparticles are prepared using bipolar electrochemistry. The potential applications of these materials as a label for protein detection are demonstrated utilizing hydrogen evolution reaction with electrochemical impedance spectroscopy as a transduction method. This new system shows high analytical performance in terms of a wide range, selectivity, sensitivity, and reproducibility.